PUBLIC HISTORY AND THE POLITICS OF MEMORY: THE 500th ANNIVERSARY OF THE BATTLE OF KOSOVO (1889) AND THE PUBLIC SHAPING OF SERBIAN NATIONHOOD - Perišić, Nikola; Kolaković, Aleksandra (Serbian political thought, 2025)
The Battle of Kosovo stands as one of the most powerful national symbols within Serbian historical consciousness and is frequently invoked in various public history practices. Considering Serbia’s current position regarding the Kosovo issue and the ongoing negotiations between Belgrade and Priština, research into the origins of the institutionalization of commemorative practices related to Kosovo and the Battle of Kosovo within modern Serbian statehood constitutes an essential component for understanding the complexity of these issues. In this context, the 1889 marking of the 500th anniversary of the Battle of Kosovo holds particular historical and symbolic significance, as it provides valuable insight into how national narratives were constructed, instrumentalized, and embedded into political culture. The paper explores the 1889 commemoration, focusing on the forms of public historical engagement that emerged during the final phase of the Obrenović dynasty. The aim is to identify patterns in the development of national historical narratives and their role in state-building processes in the late 19th century. It examines how key historical naratives centered on the Kosovo and the Serbian medieval history were constructed and mobilized for public and political purposes. The papaer employs methodologies from memory studies and the politics of memory, with particular emphasis on the early development of public history in Serbia. Special attention is given to the roles of political and intellectual actors—including Kings Milan and Aleksandar Obrenović, regents, ecclesiastical circles, historians, and intellectuals—in the organization of commemorative practices and the shaping of Serbian nationhood.
Keywords: Public History; Memory Politics; 500th Anniversary of the Battle of Kosovo; Historical Narratives; Serbian Nationhood; Identity; Nation-Building; Obrenović Dynasty; 1889